The mechanism of superheated steam affecting the quality of in-situ pyrolysates of oil shale kerogen: Part A-saturation of pyrolytic organics. (1st September 2022) - Zhao, Fumin; Li, Bao; Zhang, Lei; Che, Daochang; Liu, Shengyu
Highlights: Pyrolysis of kerogen in superheated steam was studied using ReaxFF MD simulation. The saturation of gas and light shale oil was evaluated by double bond equivalents. The path of Owater and Hwater were analyzed. The saturation of pyrolytic products was improved at superheated steam atmosphere. The H2 O involved in formation reactions of R-OH, Ar-OH, H2, NH3 and H2 S. Abstract: In this work, the effect of superheated steam on pyrolysates for in-situ pyrolysis of kerogen was investigated through ReaxFF molecular dynamics simulation in terms of the saturation of pyrolytic shale gas and light shale oil. The double bond equivalents were adopted to characterize the saturation of gas, light shale oil and the hydrocarbon. The existence form of H2 O molecules, introduced by superheated steam (named the environmental H2 O molecule, H2 Owater ), were obtained using python scripts to analyze bond order file. And the reaction pathways of several representative pyrolysates (propanol, methanol, phenols and H2 ), generated by the participation of H2 Owater molecules, were analyzed. The results indicated that, compared with pyrolysis at nitrogen atmosphere, saturation of shale gas and light shale oil were both promoted at superheated steam atmosphere, especially for the light shale oil. Under superheated steam circumstance, the inhibited dehydrogenation of kerogen is the primary reason for the saturation improvement of products. The secondary cause is the bonding of Hwater and OHwater radicals to carbon-containing radicals, which may have a hampering effect on the radical recombination reaction of short chains. During pyrolysis of kerogen with superheated steam injection, H2 Owater molecules could be involved in a serious of chemical reactions: the decomposition of char and heavy shale oil, opening reaction of heterocyclic rings, transmission and exchange of OH radicals and the formation of products (hydrocarbon, alcohols, NH3, H2 S, H2, etc.), principally via attacking radicals or fragments. The typical reactions in which H2 Owater molecules involved were given. This study would provide theoretical support for in-situ pyrolysis technology of oil shale with superheated steam injection.